Faktor-Faktor yang Mempengaruhi Kepercayaan dalam Bisnis Keluarga: Studi pada Mahasiswa Universitas Ciputra - Fahresy, Fadhil; Hakam, Dhiya Fadhila Ramadhani; Mustikarini, Carolina (Jurnal Online Manajemen ELPEI, 2025)
Trust between the founding and successor generations plays a crucial role in the success of family business succession. This study aims to identify the main factors that influence the level of trust in the family business succession process. Using a qualitative approach with a case study method, this study analyses several family businesses that are undergoing or have undergone succession. Data were collected through in-depth questionnaires with prospective successors. The results of the study revealed that there are several main factors that contribute to the level of trust in succession, namely the experience and competence of the successor, open communication between generations, early involvement of the successor in the business, transparency in decision-making, and family support. In addition, family values ​​and organizational culture also play a role in strengthening or weakening trust. The conclusion of this study confirms that building trust in succession requires a long-term strategy that involves developing successor capabilities, effective communication, and clear and structured succession planning.